(untitled) (CAHIERS MAGELLANES-NS, 2024)
The present study focuses on the formulation and characterization of phytosomes using the medicinal plant Rheum emodi, known for its therapeutic properties. Phytosomes are advanced drug delivery systems that enhance the bioavailability of herbal extracts by encapsulating them in lipid-based carriers. In this investigation, hydroalcoholic and pet ether extracts of Rheum emodi were prepared, yielding 8.22% and 0.95% respectively. Preliminary phytochemical screening of the hydroalcoholic extract indicated the presence of significant bioactive compounds, including phenolics, flavonoids, saponins, and diterpenes, which are responsible for the plant's medicinal effects. The prepared phytosomes were subjected to various characterization studies. The optimized formulation (F10) exhibited a particle size of 220.23 nm, indicating a suitable size for enhanced cellular uptake and bioavailability. The entrapment efficiency was determined to be 76.65%, suggesting a high capacity for encapsulating the active compounds from Rheum emodi. In vitro drug release studies demonstrated that the release kinetics followed the Korsmeyer-Peppas model, indicating a sustained release profile over time. This sustained release is advantageous for maintaining therapeutic concentrations in the bloodstream while minimizing side effects. These findings underscore the potential of phytosomes as an effective delivery system for herbal extracts, enhancing their bioavailability and therapeutic efficacy. The results also pave the way for future research into the application of phytosomes in herbal medicine, aiming to improve the clinical effectiveness of Rheum emodi and similar medicinal plants.